2022
DOI: 10.7759/cureus.25464
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metastasis From Glioblastoma Multiforme: A Case Report

Abstract: Glioblastoma multiforme (GBM) is the most frequent neoplasm of the central nervous system (CNS) with a low incidence in people. The heterogeneous characteristics of this malignant tumor make the overall survival one of the shortest. Metastatic lesions due to glioblastoma are mainly reported in liver, lungs and leptomeningeal spaces, existing in worldwide literature with very few reported cases. The osseous tissue continues to be an exceptional place to present metastases. This is the reason why we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The presence of CTCs in GBM has been a topic of discussion for many years. GBM is known for its high aggressiveness and invasiveness, but it predominantly remains localized to the brain, with extracranial metastases being extremely rare, affecting only 0.5-2% of patients and typically involving sites like the lungs, bone, lymph nodes, or liver [30][31][32][33][34][35][36]. Mounting evidence has shown that the presence and quantity of CTCs in bodily fluids are associated with glioblastoma progression, treatment response, and patient survival, indicating their potential as diagnostic and prognostic biomarkers.…”
Section: Circulating Tumor Cells As Glioblastoma Biomarkersmentioning
confidence: 99%
“…The presence of CTCs in GBM has been a topic of discussion for many years. GBM is known for its high aggressiveness and invasiveness, but it predominantly remains localized to the brain, with extracranial metastases being extremely rare, affecting only 0.5-2% of patients and typically involving sites like the lungs, bone, lymph nodes, or liver [30][31][32][33][34][35][36]. Mounting evidence has shown that the presence and quantity of CTCs in bodily fluids are associated with glioblastoma progression, treatment response, and patient survival, indicating their potential as diagnostic and prognostic biomarkers.…”
Section: Circulating Tumor Cells As Glioblastoma Biomarkersmentioning
confidence: 99%
“…This relatively small increase, together with better access to neurosurgery, has significantly increased the remaining life quality in GBM patients; however, it has also led to multiple reports contradicting the classical dogma that CNS tumors do not produce systemic metastasis, indicating its outdated nature, albeit with a low incidence rate compared to tumor incidence itself. Initial reports were of shunt metastasis to the peritoneum and pleura; however, in recent years, soft tissue, bone, and lymph node metastasis have also been reported in significant numbers [3,4]. These further raise the question of whether GBM is incapable of producing metastasis, based on its native cell biology; do treatment-induced and associated mutations allow for their development, or are GBM, like most other tumors, a tumor with pronoun metastatic potential, but the patients, due to its exceedingly fast growth (GBM double in size in 15-30 days), do not survive long enough for them to develop and clinically manifest?…”
Section: Introductionmentioning
confidence: 99%
“…Initial reports were of shunt metastasis to the peritoneum and pleura; however, in recent years, soft tissue, bone, and lymph node metastasis have also been reported in significant numbers [ 3 , 4 ]. These further raise the question of whether GBM is incapable of producing metastasis, based on its native cell biology; do treatment-induced and associated mutations allow for their development, or are GBM, like most other tumors, a tumor with pronoun metastatic potential, but the patients, due to its exceedingly fast growth (GBM double in size in 15-30 days), do not survive long enough for them to develop and clinically manifest?…”
Section: Introductionmentioning
confidence: 99%